2022
DOI: 10.1186/s12913-022-08827-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of peritoneal dialysis and hemodialysis in Thai population with End-stage Kidney Disease

Abstract: Background This study aimed to conduct a cost-utility analysis of the “Peritoneal Dialysis (PD)-First” policy in 2008 under a universal health coverage scheme and hemodialysis (HD) in Thai patients with End-stage Kidney Disease (ESKD) using updated real-practice data. Methods Markov model was used to evaluate the cost-utility of two modalities, stratified into five age groups based on the first modality taken at 20, 30, 40, 50, and 60 years old fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…They investigated the patients in a longer follow-up period, which might explain the discrepancies in our numbers. Researchers in Asian countries similarly calculated superior costutility of PD in their analyses [12]. The overall better cost-utility in their papers compared to ours or the one from Ferguson et al might be attributable to a generally lower cost level and especially lower wage costs in the respective countries.…”
Section: Discussionmentioning
confidence: 50%
“…They investigated the patients in a longer follow-up period, which might explain the discrepancies in our numbers. Researchers in Asian countries similarly calculated superior costutility of PD in their analyses [12]. The overall better cost-utility in their papers compared to ours or the one from Ferguson et al might be attributable to a generally lower cost level and especially lower wage costs in the respective countries.…”
Section: Discussionmentioning
confidence: 50%
“…They concluded kidney transplantation is the most cost-effective strategy, followed by PD and HD. In another study in Thailand, PD was found to be more cost-effective compared to HD based on the current WTP threshold [ 29 ]. In a study by Putri et al in Indonesia [ 30 ], PD provided good value for money versus HD for ESRD patients based on cost analysis and QALYs gained.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies reported an elevated risk of mortality of 24% to 70% with decreased kidney function ( 50 ), our finding showed much more modest risk, which may be due to the Universal Healthcare Coverage in Thailand which has been available since 2002, including peritoneal dialysis since 2008 ( 51 , 52 ). Subsidizing care improves treatment accessibility, reducing the mortality rate ( 53 55 ).…”
Section: Discussionmentioning
confidence: 99%